Naodesheng decoction regulating vascular function via G-protein-coupled receptors: network analysis and experimental investigations - Chen, Shuhan; Niu, Ziran; Shen, Yanjia; Lu, Wendan; Zhao, Jiaying; Yang, Huilin; Guo, Minmin; Zhang, Li; Zheng, Ruifang; Du, Guanhua; Li, Li (Frontiers in Pharmacology, 2024)
Introduction: Ischemic stroke (IS) is a detrimental neurological disease with limited treatment options. Recanalization of blocked blood vessels and restoring blood supply to ischemic brain tissue are crucial for post-stroke rehabilitation. The decoction Naodesheng (NDS) composed of five Chinese botanical drugs, including Panax notoginseng (Burk.) F. H. Chen, Ligusticum chuanxiong Hort., Carthamus tinctorius L., Pueraria lobata (Willd.) Ohwi, and Crataegus pinnatifida Bge., is a blood-activating and stasis-removing herbal medicine commonly used for the clinical treatment of cerebrovascular diseases in China. However, the material basis of NDS on the effects of blood circulation improvement and vascular tone regulation remains unclear. Methods: A database comprising 777 chemical metabolites of NDS was constructed. Then, the interactions between various herbal metabolites of NDS and five vascular tone modulation G-protein-coupled receptors (GPCRs), including 5-HT1AR, 5-HT1BR, β2-AR, AT1R, and ETBR, were assessed by molecular docking. Using network analysis and vasomotor experiment of the cerebral basilar artery, the potential material basis underlying the vascular regulatory effects of NDS was further explored. Results: The Naodesheng Effective Component Group (NECG) was found to induce relaxation of rat basilar artery rings precontracted using Endothelin-1 (ET-1) and KCl in vitro in a dose-dependent manner. Several metabolites of NDS, including C. tinctorius, C. pinnatifida, and P. notoginseng, were found to be the main plant resources of metabolites with high docking scores. Furthermore, several metabolites in NDS, including formononetin-7-glucoside, hydroxybenzoyl-coumaric anhydride, methoxymecambridine, puerarol, and pyrethrin II, were found to target multiple vascular GPCRs. Metabolites with moderate-to-high binding energy were verified to have good rat basilar artery-relaxing effects, and the maximum artery relaxation effects of all three metabolites, namely, isorhamnetin, kaempferol, and daidzein, were found to exceed 90%. Moreover, metabolites of NDS were found to exert a synergistic effect by interacting with vascular GPCR targets, and these metabolites may contribute to the cerebrovascular regulatory function of NDS. Discussion: The study reports that various metabolites of NDS contribute to its vascular tone regulating effects and demonstrates the multi-component and multi-target characteristics of NDS. Among them, metabolites with moderate-to-high binding scores in NDS may play an important role in regulating vascular function.